Quantitative Dietary Taurine Requirement for California Yellowtail, Seriola lalandi. Issue 1 (17th March 2017) - Salze, Guillaume P.; Stuart, Kevin R.; Jirsa, Dave O.; Davis, D. Allen; Drawbridge, Mark A.
Abstract: Although taurine has been identified as a required nutrient in several Seriola species, there are no available quantitative data on dietary taurine requirements for these commercially important species and recommendations are highly variable. Therefore, juvenile Seriola lalandi were fed one of eight practical diets supplemented with graded levels of taurine (0.11–1.08% of the dry diet, analyzed) to estimate their taurine requirement. Response in growth rate, feed efficiency, and nutrient deposition were evaluated using a broken‐quadratic model and 4‐ and 5‐parameter saturation kinetic models (4‐SKM and 5‐SKM) Blood serum composition was analyzed using linear models. Requirement estimates based on growth rates (thermal‐unit growth coefficient) and protein deposition were similar at 0.26% (95% confidence interval [CI]: 0.23–0.28) and 0.29% (95% CI: 0.25–0.34) dietary taurine, respectively. Feed and protein deposition efficiencies were optimized at 0.26–1.02% and 0.26–1.00% dietary taurine, respectively. Taurine deposition in the animal was maximized at higher dietary levels (0.64%). Levels of serum taurine increased in response to dietary levels and peaked at around 0.80% dietary taurine. Concomitantly, serum urea and total amino acid levels decreased with increasing dietary taurine levels, suggesting a reduced amino acid catabolism relative to the aforementioned improvement in protein deposition efficiency.